SUMO Localizes to the Central Element of Synaptonemal Complex and Is Required for the Full Synapsis of Meiotic Chromosomes in Budding Yeast - Voelkel-Meiman, Karen (Public Library of Science, 2013)
The synaptonemal complex (SC) is a widely conserved structure that mediates the intimate alignment of homologous chromosomes during meiotic prophase and is required for proper homolog segregation at meiosis I. However, fundamental details of SC architecture and assembly remain poorly understood. The coiled-coil protein, Zip1, is the only component whose arrangement within the mature SC of budding yeast has been extensively characterized. It has been proposed that the Small Ubiquitin-like MOdifier, SUMO, plays a role in SC assembly by linking chromosome axes with Zip1's C termini. The role of SUMO in SC structure has not been directly tested, however, because cells lacking SUMO are inviable. Here, we provide direct evidence for SUMO's function in SC assembly. A meiotic smt3 reduction-of-function strain displays reduced sporulation, abnormal levels of crossover recombination, and diminished SC assembly. SC structures are nearly absent when induced at later meiotic time points in the smt3 reduction-of-function background. Using Structured Illumination Microscopy we furthermore determine the position of SUMO within budding yeast SC structure. In contrast to previous models that positioned SUMO near Zip1's C termini, we demonstrate that SUMO lies at the midline of SC central region proximal to Zip1's N termini, within a subdomain called the “central element”. The recently identified SUMOylated SC component, Ecm11, also localizes to the SC central element. Finally, we show that SUMO, Ecm11, and even unSUMOylatable Ecm11 exhibit Zip1-like ongoing incorporation into previously established SCs during meiotic prophase and that the relative abundance of SUMO and Ecm11 correlates with Zip1's abundance within SCs of varying Zip1 content. We discuss a model in which central element proteins are core building blocks that stabilize the architecture of SC near Zip1's N termini, and where SUMOylation may occur subsequent to the incorporation of components like Ecm11 into an SC precursor structure.